Whole-mount immunofluorescence imaging and isolation of mesothelium-bound immune cell aggregates during mouse peritoneal inflammation - Ferriz, Margarita; Vega Pérez, Adrián; Gutiérrez González, Alejandra; Álvarez Ladrón, Natalia; Ardavín, Carlos (My University, 2024)
Resident peritoneal macrophages (resMØs) are crucial for repairing peritoneal injuries and controlling infections by forming mesothelium-bound resMØ-aggre gates in the peritoneal wall and omentum. Here we present a protocol to analyze these structures in mouse models of peritoneal inflammation. We describe the dissection, fixation, immunofluorescent staining, and mounting of whole perito neal wall and omentum samples and subsequent confocal microscopy imaging of resMØ-aggregates. We also detail the steps to isolate resMØ-aggregates for additional studies, including flow cytometry and electron-microscopy-based analysis.